Hypofibrinogenaemia caused by a novel FGG missense mutation (W253C) in the γ chain globular domain impairing fibrinogen secretion. Issue 9 (1st September 2005) - Vu, D; de Moerloose, P; Batorova, A; Lazur, J; Palumbo, L; Neerman-Arbez, M
Abstract : Background: Inherited disorders of fibrinogen are rare and affect either the quantity (hypofibrinogenaemia and afibrinogenaemia) or the quality of the circulating fibrinogen (dysfibrinogenaemia). Extensive allelic heterogeneity has been found for all three disorders: in congenital afibrinogenaemia >30 mutations, the majority in FGA, have been identified in homozygosity or in compound heterozygosity. Several mutations have also been identified in patients with hypofibrinogenaemia; many of these are heterozygous carriers of afibrinogenaemia null mutations. Objective: To report the case of a patient from Slovakia diagnosed with hypofibrinogenaemia characterised by fibrinogen concentrations of around 0.7 g/l. Results: The patient was found to be heterozygous for a novel missense mutation W253C (W227C in the mature protein) in the C-terminal globular domain of the fibrinogen γ chain. Co-expression of the W253C FGG mutant cDNA (fibrinogen Bratislava) in combination with wild-type FGA and FGB cDNAs showed that fibrinogen molecules containing the mutant γ chain can assemble intracellularly but are not secreted into the media, confirming the causative nature of the identified mutation. Conclusions: Current analysis of fibrinogen Bratislava indicates that the domains important for the processes of hexamer assembly and hexamer secretion should not be considered as strictly restricted to one or other fibrinogen chain.